Commons consent: Librarians, architects and community culture in co-creating academic library learning spaces. Issue 8 (9th November 2015) - Storey, Colin
Abstract : Purpose: – Constructing academic library learning spaces involves ad hoc groups of agents often with fuzzy inter-relationships. Librarians and their user communities are initially hailed within these groups as prime-movers in realizing projects. Librarians bring to the table contagious ideas generated from their own profession in the hope of securing appropriate funding and planning pre-requisites. All other agents, be they internal community representatives or external architects, assist them in making sense of each other's standpoints to co-create dynamic learning spaces in "commons consent". The paper aims to discuss these issues. Design/methodology/approach: – Using the community culture in The Chinese University of Hong Kong as existed in 2012 as a case study, this paper examines the reality of this process in terms of a new library for learning, teaching and research. Findings: – Can librarians hold sway over the priorities of other individual agents, particularly architects, to gain consent to build their initial concept of the commons which they are vigorously promoting as professionally valid and educationally potent? In the co-creation of a building, individual preferences and organizational power structures in ad hoc groups drawn from the university's distinct cultural environment fuel compromise and even tension around the librarians' and architects' original visions. Research limitations/implications: – Many other case studies of library building learning commons projects would be useful to add to these findings in sensemaking, co-creation and community cultures. Practical implications: – Assists library managers in their management of large buildings projects. Originality/value: – An original case study of a major Asian academic library learning commons project which involves sensemaking, co-creation and community cultures ideas imported from construction science.